2017
DOI: 10.1002/anie.201700178
|View full text |Cite
|
Sign up to set email alerts
|

3‐Aminodeoxypyranoses in Glycosylation: Diversity‐Oriented Synthesis and Assembly in Oligosaccharides

Abstract: A concise, diversity-oriented approach for the synthesis of naturally occurring 3-amino- and 3-nitro-2,3,6-trideoxypyranose derivatives and analogues thereof from simple sugars has been developed. In addition, we investigated the synthesis of various 3-aminoglycosyl donors and their application in glycosylation reactions. These studies led to the successful synthesis of a tetrasaccharide containing four different 3-aminosugar components using ortho-alkynylbenzoate donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 73 publications
0
37
0
Order By: Relevance
“… 102 On the other hand, Zeng, Wan, and co-workers found that fluorides were not the optimal leaving group for coupling a ristosamine donor to C-4 of a galactose acceptor. 103 As a consequence, many other classes of dexoyglycosyl donors have been developed, often mirroring donors used in conventional glycosylation reactions.…”
Section: Direct Synthesismentioning
confidence: 99%
“… 102 On the other hand, Zeng, Wan, and co-workers found that fluorides were not the optimal leaving group for coupling a ristosamine donor to C-4 of a galactose acceptor. 103 As a consequence, many other classes of dexoyglycosyl donors have been developed, often mirroring donors used in conventional glycosylation reactions.…”
Section: Direct Synthesismentioning
confidence: 99%
“…A 10 L sample was injected for each analysis. 16 Potassium carbonate (0.5 g, 3.6 mmol, 0.1 equiv) was added to a solution of tri-O-acetyl-D-glucal (10.0 g, 36.7 mmol, 1.0 equiv) in MeOH (70 mL) and the mixture was stirred at room temperature for 4 h. After completion, the mixture was filtered through Celite and concentrated on a rotary evaporator to give D-glucal as a viscous oil in quantitative yield (~5.3 g). The obtained crude product (5.3 g, 36.4 mmol) was dissolved in a mixture of dry CH 2 Cl 2 (73 mL) and dry pyridine (73 mL), cooled to 0 °C, and treated with p-toluenesulfonyl chloride (10.4 g, 54.6 mmol, 1.5 equiv).…”
Section: Syn Thesismentioning
confidence: 99%
“…Bacterial monosaccharides can feature diversely substituted amino groups, deoxy centers, carbonyl groups, and tetrasubstituted tertiary carbon atoms at various positions on the carbohydrate ring. Tertiary‐ C sugars can be found in various natural products, having attractive biological properties [7–10] . Often these tertiary C‐atoms are substituted with a small alkyl group, commonly a methyl substituent, but more complex architectures in which functionalized alkyl chains are attached can be found as well.…”
Section: Introductionmentioning
confidence: 99%